Identification of geological structure which induced heavy water and mud inrush in tunnel excavation: A case study on Lingjiao tunnel. (October 2017) - Li, Xiaozhao; Zhang, Peixing; He, Zhicheng; Huang, Zhen; Cheng, Menglin; Guo, Liang
Highlights: Misunderstanding of dangerous geostructures accounts for mud/water inrush. Epi-Fracture-Karst-Zone induced heavy mud in Lingjiao tunnel. The mechanism of mud inrush induced by EFKZ has been identified. Abstract: Groundwater and mud inrush during tunneling may cause severe security risk, great economic loss and unrecoverable damage to environment. However, the prediction and prevention still remain as a challenging problem. According to geological survey, Lingjiao tunnel was judged to be safe from danger of large-scale water and mud inrush. Unfortunately, a large (the largest one in China) mud outburst accident happened with bursting mud of more than 40, 000 m 3, leaving a huge collapse pit on the upper surface of the crossed mountain. Moreover, another mud inrush took place right in the paralleling tunnel nearby one year after the first accident, which triggered another follow-up collapse in the same site as the first time, though it has been reinforced with concrete cover. The two mud inrushes accidents were induced by and through the similar geological structure, which was not recognized. In this paper, the mud-inrush processes are expatiated. It is found that geological identification of water-bearing and mud-filling structures is crucial for subsequential effective geophysical or drilling probing, misunderstanding and unable to recognize these crucial geostructures accounts for a lot of hazards. The failure to predict the more than once mud inrushes in Lingjiao tunnel is due to misunderstanding of hazard-inducing geostructure. The water-bearing and mud-filling structure is fracture-induced karstified zone (Epi-Fracture-Karst-Zone, EFKZ) which is formed from the karstification enhanced by fracture zone rather than originally suspected main fault zone. The favorable conditions for EFKZ development and mud filling which include dissoluble rocks, hot, humid climate and dense vegetation, tensile fracture zone, thick soil and abundant rainfall and the mechanism of mud inrush have been identified: The adjacent water-bearing fillings with high pressure in EFKZ surrounding the working face flow into the tunnel when EFKZ is disturbed by blasting, which induced the heavy mud-inrush accident in Lingjiao tunnel.